Wij zijn allen broeders : leven en gedachten van Mahatma Gandhi naar zijn eigen woorden - Gandhi, Mohandas Karamchand, 1869-1948; Vogelaar, M. A.; Voillaume, René, 1905-2003 (Drachten : Laverman, 1969)
ARCHIEF. Excerpts of the writings of Mahatma Gandhi on many different topics such as: his philosophy, religion, ahimsa or nonviolence, writings on peace and poverty, on education, democracy and women.